2020 Design, Automation &Amp; Test in Europe Conference &Amp; Exhibition (DATE) 2020
DOI: 10.23919/date48585.2020.9116481
|View full text |Cite
|
Sign up to set email alerts
|

Are Cloud FPGAs Really Vulnerable to Power Analysis Attacks?

Abstract: Recent works have demonstrated the possibility of extracting secrets from a cryptographic core running on an FPGA by means of remote power analysis attacks. To mount these attacks, an adversary implements a voltage fluctuation sensor in the FPGA logic, records the power consumption of the target cryptographic core, and recovers the secret key by running a power analysis attack on the recorded traces. Despite showing that the power analysis could also be performed without physical access to the cryptographic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 9 publications
(17 reference statements)
0
16
0
Order By: Relevance
“…Multi-tenant power side-channel attacks have been investigated by Schellenberg et al [11] and Zhao et al [9]. A power analysis attack on an Amazon EC2 F1 instance [1] was successfully carried out by Glamočanin et al [7]. Furthermore, Ramesh et al [10] and Giechaskiel et al [8] demonstrated a crosstalkcoupling side-channel attack between the neighboring long wires of an FPGA.…”
Section: A Attacks In Multi-tenant Fpgasmentioning
confidence: 99%
“…Multi-tenant power side-channel attacks have been investigated by Schellenberg et al [11] and Zhao et al [9]. A power analysis attack on an Amazon EC2 F1 instance [1] was successfully carried out by Glamočanin et al [7]. Furthermore, Ramesh et al [10] and Giechaskiel et al [8] demonstrated a crosstalkcoupling side-channel attack between the neighboring long wires of an FPGA.…”
Section: A Attacks In Multi-tenant Fpgasmentioning
confidence: 99%
“…Recent studies have revealed that field-programmable gate arrays (FPGAs) available on cloud services, such as Amazon Web Services Elastic Compute Cloud (AWS EC2), are vulnerable to remotely carried out power analysis attacks [GCRS20]. These attacks can deduce secret information, such as cryptographic keys, used in remote FPGAs by monitoring the fluctuations in dynamic power consumption of a targeted victim device [GCRS20].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that field-programmable gate arrays (FPGAs) available on cloud services, such as Amazon Web Services Elastic Compute Cloud (AWS EC2), are vulnerable to remotely carried out power analysis attacks [GCRS20]. These attacks can deduce secret information, such as cryptographic keys, used in remote FPGAs by monitoring the fluctuations in dynamic power consumption of a targeted victim device [GCRS20]. In remote power analysis (RPA) attacks, an on-chip sensor that can measure the power consumption of a remote FPGA is deployed onto the targeted remote FPGA to monitor dynamic power fluctuations occurring on the FPGA.…”
Section: Introductionmentioning
confidence: 99%
“…RPA attacks have shown to be effective on the same FPGA where multiple users share the FPGA (known as multi-tenant FPGA architectures) [18], [19]. Such multi-tenanted FPGAs are expected to be common on cloud computers in future to reduce the cost of cloud-based FPGA services [20].Therefore, cloud FPGA services, such as Amazon EC2 FPGA cloud [21] and Alibaba FPGA cloud service, where FPGA acceleration is offered as a service, are vulnerable to RPAs [22]. It is imperative that countermeasures be deployed to prevent RPA attack vulnerabilities.…”
Section: Introductionmentioning
confidence: 99%